Kontekstualisasi Multikulturalisme dalam Moderasi Beragama untuk Mengonter Narasi Ekstremisme - Ahmad Khoiri (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2022)
This paper discusses multiculturalism as a crucial concept to counter extremism. The perspective used is the Islamic perspective, with the thesis that diversity is a necessity of God, so that Islam, through the Qur’an, guides human beings regarding ways of living with multicultural principles. At the same time, while some circles want a monocultural order, which is manifested by the proliferation of extremism in the name of Islam, it is as if in the Qur’an there are two contradictory teachings about plurality and how to respond to it. Based on the studies that have been carried out, this paper finds that multiculturalism is a moral-ideal of the Qur'an, while extremism is an ideological doctrine based on the interpretation of the Qur'an itself. Thus, deep multiculturalism can become a counter-narrative of extremism.